Draining and embanking a practical treatise embodying the most recent experience in the application of improved methods - Scott, John (Crosby Lockwood and Son, 1908)
The chapters of this book cover such topics as the reasons for draining land, the methods of under-draining, arrangement of drains, depth and frequency of drains, digging of drains, laying of pipes, drainage of tidal lands, and embanking.